STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH (UKM) PADA USAHA PISANG IJO DI KOTA MAKASSAR - Mariah Mariah (Jurnal Bisnis dan Kewirausahaan, 2015)
Small to medium sized Businesses are economic productive effort that is stand alone, carried out by the individual or business entity that is not a subsidiary or branch of a company which is owned, controlled, or become part either directly or indirectly with a small business or a large enterprise with a total net worth or annual sales results. The main purpose of this research is to know which variables affect the strategy of the small and medium enterprises from the third variable, product, pricing, promotion, and where the most dominant factor. This research uses descriptive methods of analysis and swot matrix of small enterprises medium-sized bananas green. Product development strategies which have been carried out by small and medium businesses is providing an affordable price, Pricing strategy development undertaken by small and medium enterprises is an affordable set prices in accordance with the wishes of consumers, promotion of development, the strategy undertaken by small and medium enterprises is building a brand that is easily recognized by the community by putting up banners and billboards. Among the three variable, there is a variable which can be developed with respect to small and medium enterprises which are product, pricing, promotion.